On the aerodynamic loads when a high speed train passes under an overhead bridge. Issue 202 (July 2020) - Liang, Xi-Feng; Li, Xiao-Bai; Chen, Guang; Sun, Bo; Wang, Zhe; Xiong, Xiao-Hui; Yin, Jing; Tang, Ming-Zan; Li, Xue-Liang; Krajnović, Siniša
Abstract: The aerodynamic loads on the overhead bridge bottom surface induced by train passage are reported in this paper. Both moving model test and numerical simulation approaches at the 1:20 scale are used. The numerical work is validated through both mesh independence tests and comparison with experimental data. Typical pressure variation curves are plotted and compared with previous studies. The peak pressure values' dependence on the Reynolds number is considered through four sets of experiments with different train running speeds. The peak pressure coefficient distribution law for the bridge bottom surface is presented. Differences in the pressure distribution in different bridge bottom areas are explained based on more detailed flow field information. The influence of the bridge height on the aerodynamic load magnitude and time interval is presented. Moreover, the application of the CEN Standard to practical engineering issues is discussed.